2016
DOI: 10.1002/hyp.11049
|View full text |Cite
|
Sign up to set email alerts
|

Pipeflow response in loess‐derived soils to precipitation and groundwater table fluctuations in a temperate humid climate

Abstract: Piping is a widespread phenomenon in the world and can significantly contribute to the downward movement of water, sediments, and nutrients. This study examines the hydrological functioning of soil pipes in a loess‐derived soil under pasture using hydrometric and hydrochemical analyses. It aims to investigate the relation between pipeflow, rainfall, and groundwater table fluctuations and to determine the dominant source of the water flowing through the soil pipes using both hydrometric and hydrochemical approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This phenomenon, which can have both natural and anthropic origin, depends on various factors such as the lithological and structural nature of the subsoil, the waterproof urban surface connected with the hydrography characteristics, the increasing "urbanization" of the subsoil (undergrounds and tram lines, underground utilities, drainage system, etc. ), the weather phenomena, the subsoil hydrogeological nature and its interaction with the mentioned factors (Waltham et al 2005;Kaufmann 2014; Vannoppen et al 2017;Bernatek-Jakiel and Poesen 2018;Bovi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, which can have both natural and anthropic origin, depends on various factors such as the lithological and structural nature of the subsoil, the waterproof urban surface connected with the hydrography characteristics, the increasing "urbanization" of the subsoil (undergrounds and tram lines, underground utilities, drainage system, etc. ), the weather phenomena, the subsoil hydrogeological nature and its interaction with the mentioned factors (Waltham et al 2005;Kaufmann 2014; Vannoppen et al 2017;Bernatek-Jakiel and Poesen 2018;Bovi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the past 40 yr, research has demonstrated the important contribution of natural soil pipes to water transfer (Jones, ). With very few exceptions, wherever the piping process has been observed there is evidence that it contributes significantly to watershed hydrology (Carey & Woo, ; Chappell, ; Holden & Burt, ; Jones, , , ; Smart et al., ; Uchida, Kosugi, & Mizuyama, ; Vannoppen, Verachtert, & Poesen, ; Wilson et al., ). However, despite these studies, the origin and hydrological functioning of soil pipes is not yet fully understood, in particular in the specific context of loess‐derived soils (Vannoppen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, water plays a crucial role in the development of soil pipes. Groundwater table fluctuation (Vannoppen et al, 2017) and subsurface flow obstruction due to mass movement (Verachtert et al, 2013) controls the soil piping. The infiltration of water and percolation into deeper soil horizons depends on the characteristics physical properties of the soil which controls the erosion rate and piping mechanism Nadal-Romero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%